Statistical mechanics of membranes and surfaces - Nelson, David R., 1951-; Piran, Tsvi, 1949-; Weinberg, Steven, 1933-2021. (Singapore ; River Edge, N.J. : World Scientific Pub., 2004)
This invaluable book explores the delicate interplay between geometry and statistical mechanics in materials such as microemulsions, wetting and growth interfaces, bulk lyotropic liquid crystals, chalcogenide glasses and sheet polymers, using tools from the fields of polymer physics, differential geometry, field theory and critical phenomena. Several chapters have been updated relative to the classic 1989 edition. Moreover, there are now three entirely new chapters on effects of anisotropy and heterogeneity, on fixed connectivity membranes and on triangulated surface models of fluctuating me.
The statistical mechanics of membranes and interfaces / David R. Nelson -- Interfaces : fluctuations, interactions and related transitions / Michael E. Fisher -- Equilibrium statistical mechanics of fluctuating films and membranes / Stanislas Leibler -- The physics of microemulsions and amphiphilic monolayers / David Andelman -- Properties of tethered surfaces / Yacov Kantor -- Theory of the crumpling transition / David R. Nelson -- Geometry and field theory of random surfaces and membranes / François David -- Statistical mechanics of self-avoiding crumpled manifolds, part I / Bertrand Duplantier -- Statistical mechanics of self-avoiding crumpled manifolds, part II / Bertrand Duplantier -- Anisotropic and heterogeneous polymerized membranes / Leo Radzihovsky -- Fixed-connectivity membranes / Mark J. Bowick -- Triangulated-surface models of fluctuating membranes / G. Gompper and D.M. Kroll.
Includes bibliographical references.
Print version record.
eBooks on EBSCOhost
Keywords: Surfaces (Physics) -- Statistical methods; Membranes (Technology) -- Statistical methods; Interfaces (Physical sciences) -- Statistical methods; Statistical mechanics; Surfaces (Physique) -- Méthodes statistiques; Membranes (Technologie) -- Méthodes statistiques; Interfaces (Sciences physiques) -- Méthodes statistiques; Mécanique statistique; SCIENCE -- Physics -- General; Membranes (Technology) -- Statistical methods; Interfaces (Physical sciences) -- Statistical methods; Statistical mechanics; Surfaces (Physics) -- Statistical methods; Membranes (Technology) -- Statistical methods; Statistical mechanics; Surfaces (Physics) -- Statistical methods